(untitled) (Comprehensive Journal of Science, 2026)
This study aims to examine the impact of applying International Financial Reporting Standards (IFRS) on enhancing the relevance and reliability of accounting information in the branches of Jumhouria, Sahara, and N0rth African banks operating in the city of Tripoli. The study adopted a descriptive-analytical approach and utilized various statistical analysis techniques through the SPSS program. The findings revealed that the banks under study adopt IFRS as their official accounting framework and comply with its requirements in recording financial transactions and preparing financial statements. The results also indicated that the application of IFRS has contributed to improving the relevance of accounting information by enhancing its ability to support economic decision-making and predict future cash flows. In addition, the implementation of these standards has strengthened the reliability of accounting information by increasing levels of neutrality and transparency in financial reporting. The study concluded that adherence to IFRS represents a fundamental factor in improving the quality of accounting information, enhancing the efficiency of financial reporting, and supporting corporate governance requirements. Furthermore, the findings showed that applying IFRS contributes to unifying accounting practices among banks and reducing discrepancies in measurement and presentation methods, thereby improving the comparability of financial statements across different financial periods. The study also emphasized that the successful implementation of IFRS depends on the availability of qualified human resources, continuous professional training for accounting staff, and the adoption of modern accounting systems and advanced digital technologies to improve the accuracy and timeliness of financial reporting. The study recommended the comprehensive and effective implementation of IFRS, modernization of accounting systems, strengthening internal control and internal audit functions, and enhancing the role of regulatory authorities. It also called for greater coordination between banks and professional bodies to ensure financial stability and reinforce users’ confidence in published accounting information.